Hubungan Dukungan Keluarga dengan Kemandirian Lansia dalam Pemenuhan Aktivitas Sehari – Hari di Wilayah Kerja Puskesmas Kec.Cikembar Kabupaten Sukabumi - Dinda Natahsya Arthamevia S; Hendri Hadiyanto; Lutyah Lutyah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Background: The elderly are an important part of the population which is increasing in number in various countries. In facing the various problems and challenges faced by the elderly, family support is very important in helping them. This support not only provides confidence and motivates the elderly to overcome the difficulties they face, the type of support provided by family members can vary from informational support, emotional support, to practical instrumental support. All of these forms of support have a significant contribution to the independence of the elderly in carrying out daily activities. The independence of the elderly is also greatly influenced by their psychological condition or mental status. Various mental disorders such as stress, depression, and fear, as well as emotional conditions such as aggression, anger, and numbness, can significantly affect an elderly person's ability to live independently. Research Objective: to identify a description of the level of independence of elderly people in providing daily activities. Research Method: The research method used in this research is cross sectional. The total sample was 74 elderly people aged 60 years and over. The instrument uses a questionnaire and the measurement instrument uses the Barthel index. The researcher's data analysis technique uses Spearman Rho. Results: shows family support for the elderly, 47 respondents (63.5%) received high family support, 27 respondents (36.5%) received sufficient family support, there were 23 respondents (31.1%) who fell into the category of dependency and 51 respondents (68.9%) were in the independent category. Using Spearman Rho analysis, the results show that the p value = 0.000 < α = 0.05 and the r value = 0.849, meaning that there is a positive and significant relationship between family support and the independence of the elderly in financing daily activities in the Cikembar District Health Center Work Area. Sukabumi Regency. Conclusion: Increasing family support for the elderly is very necessary for the independence of the elderly. Recommendation: It is hoped that the results of this research can become a reference for future researchers, and it is hoped that the community health center will provide intensive counseling to families so that they provide greater support to the elderly.